LEGO-LEGO AS PHENOMENON OF INTER-RELIGIOS AND CULTURAL IN ALOR SOCIETY - Iswanto Iswanto Iswanto (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2020)
The reality of culture is actualised in sistemic sign relation, forming perception, representing contexts, and at the highest level it functions as a portrayal of the society’s ideology (Soames, 2010). As a phenomenon, Lego-lego defines the ideology among the people of Alor. The population live in the Island of Alor and Pantar, with Kalabahi as its capital city. There are 42 indigenous languages in the area of 2864 Km² with 66.4% of the population are Protestants, 30.27% are Muslims, 3.2% are Catholics, 0.02% are Hindus, and 0.01% are Buddhists. The primary data used was the text of Lego-lego and the secondary data was the interview trascript. The theory of Dichotomy Semiotic of Ferdinand de Saussure (1993) was used. A descriptive qualitative method was used with a phenomenology approach (Gallagher, 2008). The result shows a) the sign system of inter-religious and culture in Lego-lego is divided into textual and intertextual signify where signify covers place and time as well as Alorese perception; b) diagram of cultural events in Lego-lego consists of group ideology, attitude, cultural events and contexts. It also shows that religion context is placed in the group attitude. To summarize, the interreligious and culture concept in Lego-lego are defined by using sign system and diagram of cultural events. Religion concept in Alor has become part of group attitude which is based on culture and perceived through Lego-lego discourse. Novelty in this research is the Alorese culture reflected in Lego-lego has become an extremely strong fundamental with inter-religious as one of its elements.